Nano-inclusion with uniform internal strain induced by a screw dislocation - Dai, M.; Schiavone, P.; Gao, C.-F. (Archives of Mechanics, 2016)
This paper addresses the question of whether it is possible to design a nanoinclusion (characterized here by the incorporation of interface effects along the material interface) to achieve a screw dislocation-induced uniform internal strain field when a composite is subjected to anti-plane shear deformation. We demonstrate the existence of such an inclusion by identifying its shape via a conformal mapping with unknown coefficients obtained through a system of nonlinear equations. Our numerical examples verify that the inclusion shape is dependent on its size and the specific uniform internal strain field. We show also that the inclusion shape is available even with increasing distance between the inclusion and dislocation. This latter fact leads to the additional conclusion that non-circular nano-inclusions which achieve uniform internal strain fields do indeed exist in a composite subjected to uniform remote anti-plane shear loading.